Kinetics of the dissolution of magnetite in thioglycolic acid solutions - Baumgartner, Erwin; Blesa, Miguel; Maroto, Alberto (1982)
Fil: Baumgartner, Erwin Comisión Nacional de Energía Atómica; Argentina